Total synthesis of (+)-spiroindimicin A and congeners unveils their antiparasitic activity. Issue 30 (12th July 2021) - Zhang, Zhen; Ray, Sneha; Imlay, Leah; Callaghan, Lauren T.; Niederstrasser, Hanspeter; Mallipeddi, Prema Latha; Posner, Bruce A.; Wetzel, Dawn M.; Phillips, Margaret A.; Smith, Myles W.
Abstract : Spiroindimicins A and H have been synthesized for the first time via a key palladium-catalyzed spirocyclization. Access to these alkaloids and several congeners has allowed the discovery of their antiparasitic properties. Abstract : The spiroindimicins are a unique class of chlorinated indole alkaloids characterized by three heteroaromatic rings structured around a congested spirocyclic stereocenter. Here, we report the first total synthesis of (+)-spiroindimicin A, which bears a challenging C-3′/C-5′′-linked spiroindolenine. We detail our initial efforts to effect a biomimetic oxidative spirocyclization from its proposed natural precursor, lynamicin D, and describe how these studies shaped our final abiotic 9-step solution to this complex alkaloid built around a key Pd-catalyzed asymmetric spirocyclization. Scalable access to spiroindimicins A, H, and their congeners has enabled discovery of their activity against several parasites relevant to human health, providing potential starting points for new therapeutics for the neglected tropical diseases leishmaniasis and African sleeping sickness.